The effectiveness of combined resection and radiotherapy for primary pineal malignant melanoma: a systematic review - Zhang, Jibo; Wei, Zixuan; Chen, Jincao (Frontiers in Neurology, 2024)
Objective To evaluate the effectiveness of combined resection and radiotherapy (CRAR) for the treatment of primary pineal malignant melanoma (PPMM). Methods Relevant studies were identified through a literature search in PubMed, Embase, and Web of Science from 1899 to September 1, 2023. Then we further screened the literature according to the updated PRISMA 2020 guidelines. The article information, patient information, treatment, and survival rate were analyzed. The primary outcome measures the survival rate of CRAR compared with the overall patients and the patients without treatment. Secondary outcome measures operation methods, radiotherapy methods, and dose. Results In total, 28 published articles were recorded. Among them, 35.71% (10/28) articles were on CRAR. The median overall survival, CRAR, and no treatment survival were 65, 88, and 12 weeks, respectively. The median overall survival of CRAR was demonstrably better than that of no treatment (p < 0.0001) and overall survival, even with p = 0.1177. Most of the operations adopted a supracerebellar infratentorial approach, and stereotactic radiation to tumor bed usually ranged between 50 and 60 Gy. Small dose and multiple fractions was the most popular radiotherapy method. Conclusion Currently, CRAR, compared with other treatments, is more beneficial to prolonging the survival of PPMM patients. However, many more clinical cases are needed to verify it as the best treatment approach.